Hubungan Perilaku Merokok dan Kekambuhan Asma di RSUD Cut Meutia - Sasqia Auliza Zikri; Harvina Sawitri; Nina Herlina; Nora Maulina; Baluqia Iskandar Putri (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
Asthma is a chronic inflammatory disease of the airways that remains a significant health problem because it may recur and is influenced by various triggering factors, including exposure to cigarette smoke. Smoking can worsen asthma symptoms, trigger attacks, and lead to suboptimal asthma control; therefore, an investigation of the association between smoking behavior and the recurrence level of asthma is needed. This study aimed to determine the association between smoking behavior and asthma recurrence among patients with asthma at Cut Meutia Regional General Hospital, North Aceh. This study employed an observational analytic design with a cross-sectional approach. The study subjects were 81 patients with asthma who had a history of smoking and met the study criteria, selected using purposive sampling. Smoking behavior was assessed using the Brinkman Index, while asthma recurrence or control level was assessed using the Asthma Control Test. Data were analyzed using univariate and bivariate analyses with the Chi-square test. The results showed that most respondents were aged 36–45 years, had completed senior high school education, and were self-employed. Most respondents were categorized as heavy smokers, comprising 51 respondents (63.0%), and had uncontrolled asthma, comprising 43 respondents (53.1%). Bivariate analysis showed a significant association between smoking behavior and asthma recurrence level, with a p-value of 0.001. It can be concluded that heavier smoking behavior is associated with a greater tendency toward uncontrolled asthma recurrence.